The evolution of genome size in ants - Spagna Joseph C; Suarez Andrew V; Tsutsui Neil D; Johnston J Spencer (BMC Evolutionary Biology, 2008)
Abstract Background Despite the economic and ecological importance of ants, genomic tools for this family (Formicidae) remain woefully scarce. Knowledge of genome size, for example, is a useful and necessary prerequisite for the development of many genomic resources, yet it has been reported for only one ant species (Solenopsis invicta), and the two published estimates for this species differ by 146.7 Mb (0.15 pg). Results Here, we report the genome size for 40 species of ants distributed across 10 of the 20 currently recognized subfamilies, thus making Formicidae the 4th most surveyed insect family and elevating the Hymenoptera to the 5th most surveyed insect order. Our analysis spans much of the ant phylogeny, from the less derived Amblyoponinae and Ponerinae to the more derived Myrmicinae, Formicinae and Dolichoderinae. We include a number of interesting and important taxa, including the invasive Argentine ant (Linepithema humile), Neotropical army ants (genera Eciton and Labidus), trapjaw ants (Odontomachus), fungus-growing ants (Apterostigma, Atta and Sericomyrmex), harvester ants (Messor, Pheidole and Pogonomyrmex), carpenter ants (Camponotus), a fire ant (Solenopsis), and a bulldog ant (Myrmecia). Our results show that ants possess small genomes relative to most other insects, yet genome size varies three-fold across this insect family. Moreover, our data suggest that two whole-genome duplications may have occurred in the ancestors of the modern Ectatomma and Apterostigma. Although some previous studies of other taxa have revealed a relationship between genome size and body size, our phylogenetically-controlled analysis of this correlation did not reveal a significant relationship. Conclusion This is the first analysis of genome size in ants (Formicidae) and the first across multiple species of social insects. We show that genome size is a variable trait that can evolve gradually over long time spans, as well as rapidly, through processes that may include occasional whole-genome duplication. The small genome sizes of ants, combined with their ecological, evolutionary and agricultural importance, suggest that some of these species may be good candidates for future whole-genome sequencing projects.